2003
DOI: 10.1074/jbc.m306284200
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Activator of Nuclear Factor-κB Ligand-mediated Osteoclastogenic Pathway Is Elevated in Amelogenin-null Mice

Abstract: Amelogenins, major components of developing enamel, are predominantly involved in the formation of tooth enamel. Although amelogenins are also implicated in cementogenesis, their precise spatial expression pattern and molecular role are not clearly understood. Here, we report for the first time the expression of two alternate splice forms of amelogenins, M180 and the leucine-rich amelogenin peptide (LRAP), in the periodontal region of mouse tooth roots. Lack of M180 and LRAP mRNA expression correlated with cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
102
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 47 publications
8
102
0
1
Order By: Relevance
“…1c), and the reported increase in the number of osteoclasts due to lack of amelogenins in the amelogenin KO mouse, may suggest that amelogenin has a role in the cross-talk between these two cell types controlling the process of osteoclastogenesis. It might be that amelogenin inhibits differentiation toward osteoclasts, as was suggested by Hatakeyama et al (2003Hatakeyama et al ( , 2006 for osteoclasts in the tooth supporting tissues.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…1c), and the reported increase in the number of osteoclasts due to lack of amelogenins in the amelogenin KO mouse, may suggest that amelogenin has a role in the cross-talk between these two cell types controlling the process of osteoclastogenesis. It might be that amelogenin inhibits differentiation toward osteoclasts, as was suggested by Hatakeyama et al (2003Hatakeyama et al ( , 2006 for osteoclasts in the tooth supporting tissues.…”
Section: Resultsmentioning
confidence: 90%
“…Amelogenin expression in osteocytes, osteoblasts, osteoclasts, bone marrow cells, and cartilage cells, together with the accumulating data indicating amelogenin induction of osteogenesis (Veis et al, 2000) and inhibition of osteoclastogenesis (Hatakeyama et al, 2003), suggest that amelogenin has a crucial role in the processes of bone development and remodeling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright et al (Hatakeyama et al, 2003) reported that TGF-β1 down-regulates CXCL12 expression in the stromal cell line MS-5. Similar to our studies, this decrease in CXCL12 production by MS-5 cells correlated with decreased CXCL12-dependent migratory activity (Hatakeyama et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Wright et al (Hatakeyama et al, 2003) reported that TGF-β1 down-regulates CXCL12 expression in the stromal cell line MS-5. Similar to our studies, this decrease in CXCL12 production by MS-5 cells correlated with decreased CXCL12-dependent migratory activity (Hatakeyama et al, 2003). They indicate that "primitive" mesenchymal This differentiation and maturation is mediated by RANKL, which is expressed on osteoblasts, and by receptor activator of NFkB (RANK), a cognate receptor expressed on osteoclast precursor cells (Theoleyre et al, 2004).…”
Section: Discussionmentioning
confidence: 99%